Praktik Pre-Order di E-Commerce Perspektif Akad Salam - Nursari, Nina; Nasrudin, Nasrudin; Jubaedah, Dedah; Mustofa, Mustofa (JES (Jurnal Ekonomi Syariah), 2025)
The development of digital technology has changed the pattern of economic transactions, including online buying and selling systems with pre-order schemes that are increasingly common. In the context of Islamic economics, the salam contract is a form of permissible sale and purchase with advance payment for goods delivered at a later date. This research aims to analyze the suitability of pre-order practices in online buying and selling with the principles of the salam contract in Islamic economics. This research employs a qualitative approach, utilizing a literature study method and descriptive analysis of primary and secondary sources, including DSN-MUI fatwas, and actual practices on e-commerce platforms. The results show that although there are similarities between the salam contract and the pre-order system, actual practices often deviate from the shar'i requirements, especially regarding the specifications of the goods, the certainty of delivery time, and the risk of gharar. This research offers the novelty of formulating shariah-compliant indicators for pre-order transactions based on salam contract. The main contribution of this research lies in developing an online transaction model that is more in line with maqashid sharia, as well as providing a reference for e-commerce players, regulators, and academics in realizing halal and fair digital transactions.